Programma: 16 september: Lee Clayton, Richard Cameron & band; 17 september: Roots + Ragga Night II; 18 september: Masa Depan; 19 september: The Radios (1993)
Programma: 16 september: Lee Clayton, Richard Cameron & band; 17 september: Roots + Ragga Night II; 18 september: Masa Depan; 19 september: The Radios.